2013
DOI: 10.1128/iai.00919-12
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Modulation of Enterotoxigenic Escherichia coli Virulence Genes in Response to Epithelial Cell Interactions

Abstract: h Enterotoxigenic Escherichia coli (ETEC) strains are a leading cause of morbidity and mortality due to diarrheal illness in developing countries. There is currently no effective vaccine against these important pathogens. Because genes modulated by pathogen-host interactions potentially encode putative vaccine targets, we investigated changes in gene expression and surface morphology of ETEC upon interaction with intestinal epithelial cells in vitro. Pan-genome microarrays, quantitative reverse transcriptase P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
51
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 62 publications
7
51
1
Order By: Relevance
“…More recent attempts to identify novel vaccine candidates by investigation of antigens that are transcriptionally modulated during pathogen-host interactions also highlighted eaeH, since it was strongly upregulated after contact of ETEC with intestinal epithelial cells (21). The results presented here reaffirm these findings and demonstrate the expression of EaeH by a variety of other ETEC strains.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…More recent attempts to identify novel vaccine candidates by investigation of antigens that are transcriptionally modulated during pathogen-host interactions also highlighted eaeH, since it was strongly upregulated after contact of ETEC with intestinal epithelial cells (21). The results presented here reaffirm these findings and demonstrate the expression of EaeH by a variety of other ETEC strains.…”
Section: Discussionsupporting
confidence: 78%
“…Earlier transcriptome studies demonstrated that eaeH expression is increased following epithelial cell contact (21). Accordingly, we found that shortly after attachment to host cells (5 min, Fig.…”
Section: Eaeh Encodes a Surface Molecule With Features Shared By Bactsupporting
confidence: 48%
See 3 more Smart Citations